Kenya : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2002)
This Selected Issues paper and Statistical Appendix addresses the question of how to interpret recent developments in the Kenyan consumer price index (CPI) properly to assess the current inflation pressure and extract signals about possible future CPI inflation trends. The paper discusses why Kenya's exports have performed poorly over the past five years in spite of a more liberalized trade and exchange rate regime. The analysis shows that Kenya faces both price and nonprice constraints on export performance.